2021
DOI: 10.1002/ehf2.13491
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan improves cardiac function in Chinese patients with heart failure: a real‐world study

Abstract: Aims Sacubitril/valsartan significantly reduced heart failure (HF) hospitalization and cardiovascular mortality in a randomized controlled trial. However, little is known about real-world efficacy and safety of sacubitril/valsartan in Chinese patients with HF with reduced ejection fraction (HFrEF). We aimed to evaluate whether sacubitril/valsartan could improve cardiac function in Chinese patients with HFrEF in a tertiary hospital in China. Methods and results Patients with HFrEF receiving sacubitril/valsartan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“… 13 In a similar cohort in China, only 31% of patients prescribed sacubitril/valsartan at a maximum dose of 49/51 mg twice daily after 1-year assessment. 14 In our study, 27% of patients ultimately achieved the dose of 49/51 mg twice daily after 6 months. A recent research preliminarily observed that the optimally effective and tolerated dose among Chinese patients with HFrEF was possibly lower than that among Western patients.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“… 13 In a similar cohort in China, only 31% of patients prescribed sacubitril/valsartan at a maximum dose of 49/51 mg twice daily after 1-year assessment. 14 In our study, 27% of patients ultimately achieved the dose of 49/51 mg twice daily after 6 months. A recent research preliminarily observed that the optimally effective and tolerated dose among Chinese patients with HFrEF was possibly lower than that among Western patients.…”
Section: Discussionmentioning
confidence: 51%
“…A recent research preliminarily observed that the optimally effective and tolerated dose among Chinese patients with HFrEF was possibly lower than that among Western patients. 14 This might be attributable to differences in genetic and clinical characteristics and medical treatment of patients with HFrEF between China and other areas of the world. 15 Therefore, more studies are required to further investigate and optimize dose management of sacubitril/valsartan for Chinese patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an indicator for quantitatively assessing a patient's therapeutic response would help clinicians decide whether and how much to adjust the patient's dosage of sacubitril/valsartan [36]. Moreover, a study involving Chinese patients reported a substantial reduction in renal function and increased prevalence of CKD after a median follow-up of 365 days [37]. These ndings highlight the concerning possibility that patients who are nonresponsive to sacubitril/valsartan may deriving more harm than bene t from taking the medication.…”
Section: Discussionmentioning
confidence: 99%
“…In the PIONEER-HF trial, early treatment of lcz696 in patients with MI reduced the level of N-terminal pro-B-type natriuretic peptide and alleviated LV systolic dysfunction [ 24 ]. The PARADISE-AMI study also showed that patients with acute MI benefit from the lcz696 treatment [ 25 ], and studies are emerging to analyze the treating effect of lcz696 on MI and heart failure [ 15 , 26 ]. Moreover, several studies reported that the molecular changes are involved in the biofunctions of lcz696.…”
Section: Discussionmentioning
confidence: 99%